Balance-akte 88 : Neue Kunst aus Niederösterreich. - Wagner, Manfred (Wien : Niederösterreichisches Landesmuseum, 1988)
Damisch, Gunter ; Danner, Josef ; Denk, Wolfgang ; Klein, Alex ; Kowanz, Brigitte ; Kupelwieser, Hans ; Linke, Gert ; B., Ona ; Pellikan, Christina ; Rainer, Helmut ; Scheidl, Roman ; Steiner, Herwig ; Vopava, Walter ; etc.
Balance-akte 88 : Neue Kunst aus Niederösterreich, Niederösterreichisches Landesmuseum, Wien, 1988
Duits
kunstcatalogus
Keywords: Oostenrijk